The Role of Anti- Cathapsin G among Patients with Rheumatiod Arthritis - Al-Rubaye, Mahmood R.; Abdul-Qader, Sajid N.; Abdul–majeed, Nahla G.; Kamil, leen K. M. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: Perinuclear Antineutrophil Cytoplasmic Autoantibodies (pANCA) have been found in patients with rheumatiod arthritis. Cathepsin G was the major target antigen.The present study was to investigate the unknown target antigen of ANCA (Cathapsin G ) in patients with rheumatiod arthritis Objective: This study is to investigate the prevalence of anti-Cathapsin G and rheumatoid factor in Iraqi patients with rheumatiod arthritis. Patienties&Methods: From1st January until 30 June of 2011 fourty five rheumatiod arthritis patients referred to the immunological department in the teaching laboratory of medical city and twenty five apparently healthy individual used as a control group were investeged to rheumatic factor IgG, IgM ,IgA isotypes and anti-Cathapsin G were measured by using enzyme immunoassay technique. Result: This study showed that the age of patients with rheumatiod arthritis ranged between eigthen years and sixty six years with mean age of (36.08) , while the mean level for RF screen, RF IgG, RF IgM, RF IgA isotypes and anti-Cathapsin G were (160.71, 91.7, 136.64, 95.03 and > 9.2 ) respectively. There were 17(37.8%) males and 28(62.2%) females of RA patients. Immunologically, this study revealed that the serum RF screen was found more than 25 U/ml in all rheumatiod arthritis patients (100%, P: 0.0001 HS). On the other hand RF isotypes IgG ,RF IgM and IgA level were elevated more than 20 U/ml and it was detected in 31 (68.9%, P: 0.0001 HS), 31 (68.9%, P : 0.0001 HS) ,and 32 (71.1%, P: 0.0001 HS) patients respectively, while the rheumatiod factors (IgG,IgM, and IgA)were normal in healthy control group . Statistically RF screen has a highly significant association with RF IgG, IgM, and IgA (P= 0.0001). Anti-Cathapsin G was found in 12(26.7%, P value: 0.019) of patients with rheumatic arthritis patients. This study showed a association between the positive result of anti-Cathapsin G with RF IgG and RF IgM (35.5%, P: 0.047) the results were the same for both, while no association found with RF IgA (25%, P: 0.692). Conclusion: A significant correlation was found between anti-Cathapsin G and patients with rheumatiod arthritis and has a significant association with RF IgG and RF IgM while RF IgA had no relation with anti-Cathapsin G.